Political Parties in Singapore, Malaysia, and the Philippines: Reflection of Democratic Tendencies - Fionna, Ulla (UI Scholars Hub, 2008)
This essay examines the role of political parties in different forms of government. In the three Southeast Asian countries, the different governments have distinctive methods of utilizing the parties according to their needs. The more democratic the country usually the less control the government has on the parties. The more reliant the government on its party, the more systematic its control over it. Consequently, the stronger control of government the less likely the parties would be able to reach democracy.